Oral History Interview: Pioneer Memory Days The Telephone Company Estell Campbell interviewed by Charlotte Torrey - Campbell, Estell; Torrey, Charlotte
Estell Campbell was born on December 10th, 1910 in Porterville, California. In 1936 Campbell moved to Bakersfield, California and began working for the American Telephone and Telegraph company (AT&T). His career spanned from 1936 to 1971 in which time he held several positions including repairman, installation foreman, and cut-over supervisor. Campbell discusses the technical aspects of working with early telephone equipment as well as the quick advances in technology that were made in the field during his career.